The digitalization of films in the folk music archive at the Institute of Art Studies – the ethnomusicologist’s point of view (Research Announcements "Heritage BG", 2025)
This text presents part of a more extensive study on theory and practice of ethnomusicological fieldwork with camera in Bulgaria between 1953 and 1965. The article seeks to outline one of the first ethnomusicological problems during the digitalization of stored rites and dances recorded without sound cameras and integrated synchronic sound recorders: identification of the sound associated with the footage, the various relations between picture and sound in the every single record, and hence – the possible options for their synchronization in the digitalization process. The paper places the problem in the field of the inextricable connection between the dominant research methodology and the available audio- and filming technologies in the ethnomusicological fieldwork during the considered period, with which it also presents a part of the history of Folk Music Archive at the Institute of Art Studies. References:Botuscharov 1973: Botuscharov, Luben. Vaprosi na katalogizatsiyata na muzikalniya folklor v arhiva na Instituta za muzikoznanie pri BAN. Sofia: Institute of Musicology, manuscript.Djoudjeff 1980: Djoudjeff, Stoyan. Balgarska narodna muzika. Tom 1. Sofia: Muzika.Naydenova 2021: Naydenova, Goritza. Terenni videozapisi ot 50-te godini na XX vek v Muzikalnofolklorniya arhiv na Instituta za izsledvane na izkustvata: stapki kam predstavyaneto im v digitalna sreda. – Research Announcements. Bulletin “Heritage BG” 1/2021, ed. Emmanuel Moutafov. Sofia: Centre of Excellence ‘Heritage BG’, 82-89.Naydenova 2024: Naydenova, Goritza. Terennite videozapisi na traditsionni obredi, muzika i tants v Bulgaria i razvoyat na balgarskata muzikalna folkloristika mezhdu 1954 i 1965. Sofia: IAS, manuscript.Elschek 1966: Elschek, Oskár. Methodological Problems in Slovak Ethnomusicology. – Ethnomusicology, Vol. 10, No. 2, 191-198.Elschek 1989: Elschek, Oskar. Film and Video in Ethnomusicological Research. – The World of Music, Vol. 31, No. 3, 21-37.Feld 1976: Feld, Steve. Ethnomusicology and Visual Communication. – Ethnomusicology, Vol. 20, No. 2, 325.Karácsony 2016: Karácsony, Zoltán. Filmtár. In: Fügedi János, Karácsony Zoltán, Máté Zsuzsanna, Varga Sándor. Az MTA BTK Zenetudományi Intézet Néptánc Archívuma. https://zti.hu/files/folk_neptanc/l01772.pdf (15.05.2024).Sources:Scientific Archives, BAS, f. 83, op. 1, а.е. 41Scientific Archives, BAS, f. 83, op. 1, а.е. 89
Keywords: ethnomusicology; ethnochoreology; fieldwork with camera; folkloristic film archive; sound; synchronization